A Case Report on Oral Subcutaneous Dirofilariasis. (17th December 2015) - Jayasinghe, R. D.; Gunawardane, S. R.; Sitheeque, M. A. M.; Wickramasinghe, S.
Abstract : Dirofilariasis is an uncommon zoonotic parasitic infection affecting human. The natural hosts for this nematode are animals such as dogs, cats, foxes, jackals, and raccoons. This disease is endemic in South Eastern United States, Australia, Europe, and Central and Southern Asia. Dirofilaria immitis and D. repens are the common mosquito borne filarial nematodes that cause infection. Several species of mosquitos including Mansonia uniformis, M. annulifera, and Aedes aegypti are the potential vectors for this disease in Sri Lanka. Two rare cases of dirofilariasis presenting as facial and intraoral lumps are presented.